Boomi's boombox (Katherine Tegen Books, HarperCollins, Katherine Tegen Books, an imprint of HarperCollins Publishers, 2023)
Twelve-year-old Boomi accidentally travels back in time to 1986 Thumpton-on-Soar, England, where she meets her late father as a child, changing her life forever.

The secret explorers and the haunted castle (The Secret Explorers, 11,, 2022)
"Kiki the engineering explorer and Gustavo the history expert get caught up in a spooky adventure when a ghostly figure shows up at a castle before a big tournament"--Provided by publisher.

The last phoenix (HarperCollins Publishers, Harper, 2010)
Four stepsiblings travel through time and space to help a scatterbrained phoenix gather the materials she needs to hatch her egg.

The blue ghost (Random House, 2005)
At her grandmother's log cabin, nine-year-old Liz is led to make contact with children she believes may be her ancestors.

The house with a clock in its walls (Lewis Barnavelt mysteries, ,, 2018)
"When Lewis Barnavelt, an orphan, comes to stay with his uncle Jonathan, he expects to meet an ordinary person. But he is wrong. Uncle Jonathan and his next-door neighbor, Mrs. Zimmermann, are both magicians. Lewis is thrilled. At first, watching magic is enough. Then Lewis experiments with magic himself and unknowingly resurrects the former owner of the house: a woman named Serenna Izard"--Back cover.

The backward season (Wishing Day, ,, 2018)
Ava Blok travels back in time to fix her family.

Abe Lincoln at last! (Magic tree house, 47,, 2011)
The magic tree house whisks Jack and Annie to Washington D.C. in the 1860s where they meet Abraham Lincoln and collect a feather that will help break a magic spell.

Thanksgiving on Thursday (Magic tree house, 27,, 2002)
Jack and Annie travel in their magic tree house to the year 1621, where they celebrate the first Thanksgiving with the Pilgrims and Wampanoag Indians in the New Plymouth Colony.

The artifact hunters (Viking, 2020)
During World War II, a Czechoslovakian Jewish boy is sent to northern Scotland to live in a castle that houses gifted children who are learning to harness their magical powers to support the Allies' cause.

Saving the Stegosaurus (DK Publishing (Dorling Kindersley), 2022)
In this adventure, Jamie and Tess find themselves caught in a terrible storm. During the chaos, a stegosaurus egg is swept away downriver. It's up to Jamie and Tess to recover the egg and return it to its mother before it's too late!--

Dogs in the dead of night (Magic tree house, 46,, 2011)
Jack and Annie travel to a monastery in the Swiss Alps where, with the help of St. Bernard dogs and magic, they seek the second of four special objects necessary to break the spell on the wizard Merlin's beloved penguin, Penny.

The Fran that time forgot (Franny K. Stein mad scientist, 4,, 2005)
When her embarrassing middle name is revealed at school, mad scientist Franny K. Stein experiments with time in order to return to the past and give herself a more dignified name.

The last present (Willow Falls, 4,, 2017)
Children's birthdays are always strange in Willow Falls, but when Connor's little sister Grace falls into a frozen state on her tenth birthday, Amanda and Leo must travel back in time to find out what force prevented Angelina from casting the blessing that would have protected her.

Proof of forever (HarperCollins, HarperTeen, an imprint of HarperCollinsPublishers, HarperCollins Publishers, 2015)
"Four former friends are transported back in time to a pivotal summer in all of their lives during a camp reunion"--

T. Rex time machine (T. Rex Time Machine, ,, 2019)
Two very hungry dinosaurs discover a time machine and are instantly transported to America in 2018, where they are delighted to find themselves surrounded by food (including pizza and doughnuts), but soon less excited to find themselves surrounded by policemen with guns--so they escape to the time machine, not knowing where it will take them next.

Days of the knights (Tales of the time dragon, 1,, 2014)
Red the Time Dragon transports Joe and Lilly to England, around 1200 A.D., to teach them about life in the Middle Ages.

Ben Franklin's in my bathroom! (Schwartz & Wade Books, 2017)
When ten-year-old Nolan and his little sister, Olive, find Ben Franklin in their kitchen, they do their best to guide Ben through the new world he helped form.

Sunset of the sabertooth (Magic tree house, 7,, 1996)
The magic tree house transports Jack and Annie on a mission to the Ice Age where they encounter Cro-Magnons, cave bears, sabertooth tigers, and woolly mammoths.

The time of the fireflies (Scholastic Inc., Scholastic Press, 2014)
When Larissa Renaud starts receiving eerie phone calls on a disconnected phone in her family's shop, Bayou Bridge Antiques, she finds herself directed to the river bank near her house, where a cloud of fireflies take her on a journey through time to learn the secrets of her family's past--and save their future.

Monsters on the run (The Yeti files, ,, 2015)
Yeti Blizz Richards and his gang of cryptids set out to find a friend for Vanessa, the Loch Ness Monster, even though it means traveling back in time to the dangerous age of the Cretaceous looking for plesiosaurs--unfortunately Vanessa proves to be rather timid about meeting other dinosaurs.